Producción de tomate (Lycopersicum esculentum mill) con la aplicación de dos abonos orgánicos foliares y edáficos en el Centro Experimental La Playita de la Universidad Técnica de Cotopaxi Extensión la Maná. 2015 - Sigcha Cunuhay, Rigoberto Fernando (2016)
In order to evaluate production of tomato (Lycopersicum esculentum Mill.) with two leaf application of organic fertilizers and soil an essay in La Playita Experimental Center of the Cotopaxi Technical University where the vermicompost were employed was raised and bocaschi (soil fertilizers 5kg m2) and humic acid and Agrostemin (cc foliar fertilizers 1 liter of water) on plots of 3,10 m long by 2,00 wide distributed design of randomized complete block with a total of seven treatments, four replications and nine plants as experimental unit, it was shown that most plant height was recorded in the treatment bocaschi more humic acid with 138,34 cm to 165,83 cm 45 days and treatment with acid humus + Humic 60 days, the highest number of flowers was presented in humus with 9,09; the largest total number of fruit was exposed to the treatment of worm humus + humic acid with 23,88....